Analysis of the Implementation of Bureaucratic Reform Policy in the Ministry of Home Affairs - Rangga Wilis Chaniago; Muhadam Labolo; Andi Pitono; Ahmad Averus (Jurnal Scientia, 2024)
Bureaucratic reform that has been implemented by the government for more than 10 years as an effort to reform and change various aspects of government administration is not getting closer to the expected goals. This can at least be seen from the value of the Community Satisfaction Survey (SKM) and the Corruption Perception Index which continues to decline. The Ministry of Home Affairs in implementing bureaucratic reform has a significant role because it is included in the National Bureaucratic Reform Team. However, the gap in this research stems from the value of the Bureaucratic Reform Index in the Ministry of Home Affairs from 2015 to 2022 which tends to be stagnant and continues to show a wide gap between the results of the RB index and the targets set in the Ministry of Home Affairs' Strategic Plan. This research uses the Policy Implementation theory according to George Edward III as a basis for analysis. Researchers focus on the dimensions of communication, resources, disposition and organizational structure of policy. Next, describe the supporting and inhibiting factors in policy implementation and produce efforts to overcome existing obstacles. The method used in this research is descriptive qualitative, with the researcher as the research instrument, data collection techniques using interviews, documentation and observation, snowball sampling techniques for selecting informants, data analysis through reduction, presentation and drawing conclusions supported by triangulation of sources for data validity. The research results show that the implementation of reforms in the Ministry of Home Affairs in 2023 has shown quite optimal results. This is shown by the RB Index value which was able to increase significantly by 5.02 points or 84.19 (satisfactory with the record). However, the results obtained were still below the strategic plan target, namely 91.01 (satisfactory). The inhibiting factors can be seen in the lack of influence of the simplification of the organizational structure on work culture and the implementation of the fragmentation of responsibilities related to digitalization which actually leads to overlapping applications. In addition, the risk of corruption is still in the "vulnerable" category. To overcome these obstacles, this is done by implementing a new work system evenly in each work unit, developing corruption prevention through integrity zones and using big data as a data integration effort.